SMAD4 alteration associates with invasive‐front pathological markers and poor prognosis in colorectal cancer. Issue 6 (1st April 2019) - Oyanagi, Hidehito; Shimada, Yoshifumi; Nagahashi, Masayuki; Ichikawa, Hiroshi; Tajima, Yosuke; Abe, Kaoru; Nakano, Masato; Kameyama, Hitoshi; Takii, Yasumasa; Kawasaki, Takashi; Homma, Kei‐Ichi; Ling, Yiwei; et al.
Abstract : Aims: SMAD4 acts as a tumour suppressor, and the loss of SMAD4 is associated with poor prognosis in colorectal cancer (CRC) patients. Although next‐generation sequencing (NGS) enabled us to detect numerous genetic alterations in a single assay, the clinical significance of SMAD4 alteration detected with NGS has not been fully investigated. The aim of this study was to evaluate the clinicopathological characteristics and clinical significance of SMAD4 alteration detected with NGS in CRC. Methods and results: We retrospectively investigated 201 patients with stage I–IV CRC, by using a 415‐gene panel. To analyse the relationship between SMAD4 alteration and other clinicopathological characteristics, we evaluated clinicopathological variables, including invasive‐front pathological markers: tumour budding, poorly differentiated cluster, and Crohn‐like lymphoid reaction. Fifty‐six patients (28%) had SMAD4 alteration: 24 and 32 patients had SMAD4 mutation and deletion, respectively. SMAD4 alteration was significantly associated with T category ( P = 0.027), N category ( P = 0.037), M category ( P = 0.028), and invasive‐front pathological markers, such as poorly differentiated cluster grade 3 ( P = 0.020) and absence of Crohn‐like lymphoid reaction ( P = 0.004). Immunohistochemistry revealed that SMAD4 alteration was significantly associated with loss of SMAD4 ( P = 0.023). In 90 patients with stage I–III disease, SMAD4 alteration was significantly associated with poor prognosis for relapse‐free and overall survival ( P = 0.047; P = 0.022, respectively). Conversely, in 111 patients with stage IV disease, SMAD4 alteration was not significantly associated with overall survival. Conclusion: SMAD4 alteration is associated with invasive‐front pathological markers and poor prognosis in stage I–III CRC patients.